Skutečnost a subjekt - Benyovszky, Ladislav (Lidé města, 2001)
The study follows up the reflection "Historical basis of the transformation of soul into spirit." lt shows that Descartes' concept of man as the "narrowest link of soul and body" did not yet fully arrive at the approach to the human species as a subject, as an acting individual, because it was unable to consider the human body differently than from the mechanistic point of view. According to the study the shortcoming arises from the fact that Descartes did not approach the being as reality. This only happened by Spinoza. This is why the study centered on an interpretation of Spinoza's concept of being as reality. The examination is made in the form of an interpretation of Spinoza's famous argument 29 in the first part of Ethic. The reflection is an immediate continuation of the study "Reality and subject." It thoroughly analyses individual structural aspects of Spinoza's concept of reality: substance-mode; freedom-necessity; God-attribute-final thing; the cause itself. On the strength of this it shows a transformation in the concept of an individual thing - it is understanding from conatus as an inherent characteristic. It shows that it has thus prepared a way to a unified approach to man as an acting individual. The paper leads to the reflection that Spinoza was the first to regard the man as a subject.